Study Of Different Nitrogen Level On Growth And Yield Attributing Characters Of Radish (Raphanus Sativus L.) Cv. Arka Nishant (International Journal of Food and Nutritional Sciences, 2022)
The present investigation entitled “Effect of nitrogen level on growth and yield Attributing character of radish (Raphanus sativus L.) cv. Arka Nishant ” was carried out during Rabi season in the year 2022-23 at Research plot of Department of Horticulture at Rama University Kanpur. The experiment was laid out in Randomised Block Design with eight treatments randomized thrice. Arka Nishant variety was taken to study best suitable combination of Nitrogen to get highest yield in radish. The Different Nitrogen level used viz., N0 (Control); N1 (55 kg Nitrogen/ha); N2 (75 kg Nitrogen/ha); N3 (95 kg Nitrogen/ha); N4 (115 kg Nitrogen/ha); N5 (135 kg Nitrogen/ha); N6 (155 kg Nitrogen/ha) and N7 (175 kg Nitrogen/ha).It is observed from the investigation that the treatment N4- 115 kg Nitrogen/ha gave the highest growth and yield parameters viz., Plant height at 15 DAS, 30 DAS and at harvest(14.84,27 and 66.16 cm), number of leaves per plant at 15 DAS, 30 DAS and at harvest(6.72,9.84and 17.10), Fresh weight of leaves at 15 DAS, 30 DAS and at harvest (44.10,83.28 and 118.32gm), Leaf area per plant at 15DAS, 30 DAS and at harvest (41.20,132.54 and 170.64cm2), Length of leaves at harvesting(38.22cm), Root length (26.78cm), Root girth (12.10cm), Average plant weight at Harvesting (224.15gm), Fresh root weight (150.45gm/plant), Yield per plot (34.15kg) and Yield per hectare (376.52q) respectively. While, the minimum results were found under N0 (Control) for all the parameters. So, we can suggest to farmers that the dose of 115 kg Nitrogen/ha gave the better results in term of growth and yield of Radish.